Implementing models of financial derivatives object oriented applications with VBA - Webber, Nick (Wiley finance series., 2011)
"A practical, step-by-step introduction to the design of pricing engines with VBA This book teaches students and practitioners the numerics and design of a powerful pricing tool in VBA. It leads the reader through the basics of VBA, from simple procedural code to the advanced design of systems and object-style applications. It also covers Monte Carlo and lattice methods and their implementation in VBA. Full implementation methods and code are provided for all methods discussed, making this an invaluable guide for portfolio managers, risk managers, and fund managers. Nick Webber (Warwick, UK) is a lecturer in finance at Warwick Business School. He specializes in interest rate modeling and computational finance"--